If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 52x + 8y + -13x + -19y = 0 Reorder the terms: 52x + -13x + 8y + -19y = 0 Combine like terms: 52x + -13x = 39x 39x + 8y + -19y = 0 Combine like terms: 8y + -19y = -11y 39x + -11y = 0 Solving 39x + -11y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11y' to each side of the equation. 39x + -11y + 11y = 0 + 11y Combine like terms: -11y + 11y = 0 39x + 0 = 0 + 11y 39x = 0 + 11y Remove the zero: 39x = 11y Divide each side by '39'. x = 0.2820512821y Simplifying x = 0.2820512821y
| -7(7m-6)-2(-8m+4)=-65 | | 94.2*3.14=15r | | 4x+6=-2x+14 | | 94.2*3.14=30 | | 5x-2.6x+7.2= | | 4-(4/z)=7 | | 6x+29=16x-17 | | 8(-8n+4)-(n-8)=40 | | 1/4+4x/5-11/20 | | 2+i=0 | | 2y-9=24+2y | | 4x+2=38-3x+x | | x+(x*0.1)=2 | | 6=4y-3.2x | | mx^2+6x+1=0parametre | | x+(x*1)=2 | | x+(x+1)=2 | | mx^2+6x+1=0discution | | 3(5-3(4-q))-5=5(3(5q-4)+2)-26 | | x^3+6yx^2+11xy^2+6y^3=0 | | 4b+3b+(b+12)=180 | | -24=3(2x+2) | | 64+(2y)+(2y)=180 | | 3x-45=3(3x+5) | | 64+2y+2y=180 | | (w+12)+(5w+15)+(3w-9)=180 | | 2b+hP=t | | 4x^2-33x+37=-8+1 | | 31+(2s-10)+(2s-13)=180 | | -2+p/3=9 | | 3p+(2p-45)+(2p-50)=180 | | 5m-5=-5-5m-m |